Odd and Even Ratio Edge Antimagic Labeling (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
In this paper we introduce a new labeling namely odd and even ratio edge antimagic labeling and study the existence of this labeling for basic graph structures .